Spatio-temporal assessment of gully activity in Namibia using Sentinel-1 SAR and Tandem-X DEM products as an instrument for land degradation neutrality - Vallejo Orti, Miguel; Castillo, Carlos; Bubenzer, Olaf; Höfle, Bernhard; Negussie, Kaleb Gizaw (AGU Fall Meeting 2021, 2021)
Gully erosion is one of the most dangerous environmental threats in (semi-) arid regions. In Africa, changes in rainfall and unfavourable land-use practices have accelerated gully growth in recent decades, leading to landscape fragmentation, unbalanced watersheds runoff dynamics and desertification. National and international organizations have undertaken plans to reverse this catastrophic development. Therefore, the identification and development of standardized measurement and analytical procedures to quantify gully changes is a great necessity. The democratization of Uncrewed Aircraft Vehicles (UAV) has generated new possibilities to derive detailed 4D models (i.e. 3D surface changes over time). However, gullies frequently affect very large and inaccessible areas, as is the case of Namibia, and more remote and scalable solutions are required. Sentinel-1 radar sensors offer possibilities to study physical soil features and small-scale terrain deformation patterns through the signal backscattered intensity (sigma) and the electromagnetic wave phase coherence. Time series of both variables were studied in a large gully in Namibias Kunene Region between July 2019 and June 2021, incorporating two rainy seasons. As radar coherence is higher in gully zones due to the high soil compaction and the consequent lack of vegetation, low coherence periods is a proxy of terrain changes and gully activity. In this sense, comparing 19/20 and 20/21 wet seasons, the first one was more active in its erosion activity, as coherence was 10-15% lower in the gully areas. These results correlate well with the closest meteorological station records, which registered a much higher rainfall in 2019/2020 (>300 mm) than in 2020/21 (<100 mm). Zonal analysis confirms through the absolute differences in sigma images between the beginning and end of each season that the 19/20 season was more active in the gully areas than the 20/21. This result indicates greater activity in the east margin of the gully especially in the zones close to its external walls, with a more stable interior area. Preliminary findings show good temporal linking with rainfall rates, however, accurate validation is required for the zonal analysis using ultra-high resolution UAV imagery and 3D point clouds captured in the study area before and after each rainy season.